PENGARUH KATALIS ASAM (H2SO4) DAN SUHU REAKSI DALAM PEMBUATAN BIODIESEL DARI LIMBAH MINYAK IKAN - Boby Gusman Irianto Samosir; Fradriyan Aulia; Luqman Buchori (JURNAL TEKNOLOGI KIMIA DAN INDUSTRI, 2012)
Biodesel is a fuel that consists of a mixture of monoalkyl esters of long fatty acid used as an alternative for. The purpose of this study was to produce biodiesel using fish waste as raw materials and the influence of the acid catalyst and reaction temperature on biodiesel specifications. For fixed variables consist of: weight of fish oil, cooking time, comparison of oil content of methanol, catalyst wt%, while variable changes consist of: the amount of acid catalyst, and reaction temperature. Variation of catalyst used in this study were 1 ml, 2 ml, 3 ml, and 4 ml, while the variation for the reaction temperature is 50oC, 60oC, 70oC and 80oC. In this study consists of two stages. The first stage is making biodesel which consists of: preparation and analysis of fish oils, esterification and transesterification of triglycerides and glycerol separation. In the second phase is to analyze the physical properties biodesel result of transesterification The results obtained that the change in temperature and amount of catalyst H2SO4 affect the yield value, viscosity, density and refractive index of biodiesel. The changes affect the amount of catalyst H2SO4 calorific value of biodiesel. In the process of making biodiesel from fish oil obtained results close to Test for specific gravity, viscosity and refractive index is a variation of temperature (70oC, 80oC; amount of catalyst H2SO4 1 ml, 2 ml, 3 ml, 4 ml) and variations in temperature (60oC amount of catalyst 3 ml, 4 ml). The calorific value of biodiesel from fish oil every variation of catalyst amount is far below the heating value of SNI, which is between 5190 - 5575 kcal / kg.